Gain of chromosome 21 increases the propensity for P2RY8::CRLF2 acute lymphoblastic leukemia via increased HMGN1 expression - Page, Elyse C.; Heatley, Susan L.; Rehn, Jacqueline; Thomas, Paul Q.; Yeung, David T.; White, Deborah L. (Frontiers in Oncology, 2023)
Acute lymphoblastic leukemia (ALL) patients with a gain of chromosome 21, intrachromosomal amplification of chromosome 21 (iAMP21), or Down syndrome (DS), have increased expression of genes in the DS critical region (DSCR) of chromosome 21, including the high-mobility group nucleosome-binding protein 1, HMGN1. Children with DS are predisposed to develop hematologic malignancies, providing insight into the role of chromosome 21 in the development of leukemias. A 320-kb deletion in the pseudoautosomal region of the X/Y chromosome in leukemic cells, resulting in a gene fusion between the purinergic receptor and cytokine receptor-like factor-2 (P2Y Receptor Family Member 8 (P2RY8)::CRLF2), is a common feature in 60% of DS-ALL and 40% of iAMP21 patients, suggesting a link between chromosome 21 and P2RY8::CRLF2. In an Australian cohort of pediatric B-ALL patients with P2RY8::CRLF2 (n = 38), eight patients harbored gain of chromosome 21 (+21), and two patients had iAMP21, resulting in a significantly increased HMGN1 expression. An inducible CRISPR/Cas9 system was used to model P2RY8::CRLF2 and investigate its cooperation with HMGN1. This model was then used to validate HMGN1 as an influencing factor for P2RY8::CRLF2 development. Using Cas9 to cleave the DNA at the pseudoautosomal region without directed repair, cells expressing HMGN1 favored repair, resulting in P2RY8::CRLF2 generation, compared with cells without HMGN1. CRISPR/Cas9 P2RY8::CRLF2 cells expressing HMGN1 exhibit increased proliferation, thymic stromal lymphopoietin receptor (TSLPR) expression, and JAK/STAT signaling, consistent with cells from patients with P2RY8::CRLF2. Our patient expression data and unique CRISPR/Cas9 modeling, when taken together, suggest that HMGN1 increases the propensity for P2RY8::CRLF2 development. This has important implications for patients with DS, +21, or iAMP21.